District officials' perspectives regarding factors that impede the attainment of quality basic education in a province in South Africa. Issue 6 (18th August 2019) - Bantwini, Bongani D.
ABSTRACT: The provision of quality basic education is essential as it can ensure that all learners have an equal opportunity to succeed in life. This paper discusses district officials' perspectives regarding some factors that impede the achievement of quality basic education in schools under their jurisdiction. Data were collected through semi-structured interviews conducted with district officials in eight districts in one province of South Africa. Data analysis followed the iterative approach. Findings reveal that district officials viewed the state of education in their districts and circuit as unsatisfactory due to: low teacher morale, schools' lack of confidence in their districts and the perceived neglect of the General Education and Training Band. It is argued that improved teacher working conditions, use of better service delivery model by the districts and education department, and full prioritisation of the GET Band are needed in these districts. In conclusion, to achieve social justice in education, corrective measures should be premised upon the understanding of the social and contextual issues as these represent the crippling factors in the province.